Isolation of aerobic bacteria from the lungs of chickens showing respiratory disorders and confirmation of Pasteurella multocida by polymerase chain reaction (PCR) - Ozbey, Gokben; Muz, Adile (My University, 2006)
In this study, lung samples of chickens slaughtered at an abattoir in Elazig province were tested for the presence of Pasteurella multocida and other aerobic bacteria. The identity of P. multocida was proved by mouse pathogenicity test and polymerase chain reaction (PCR). A total of 2000 chickens were examined at post-mortem, and 250 samples with pneumonia were collected. All lungs were collected from 10 different commercially reared chicken flocks showing respiratory disorders. Blood agar supplemented with 7% sheep blood was used for isolation of the agents. Of the examined chicken lung samples 16 (6.4%) P. multocida were isolated and identified. In addition, mouse pathogenicity test was carried out on P. multocida suspected isolates. Twelve (75%) of isolates were all positive. All P. multocida-suspicious isolates were positive in PCR. However, toxigenic P. multocida were not detected using PCR primers derived from toxA gene. This study showed that P. multocida is not widespread among the chicken population in Elazig.
Keywords: Chicken; Lung; P. multocida; Polymerase chain reaction